Kajian Yuridis Pengembalian Barang Bukti Oleh Judex Juris Dalam Perkara Pencurian Dengan Kekerasan - Hangga Tri Aditya (Sebelas Maret University, 2017)
Research aims to examine and answer the conformity an appeal reasons by public prosecutor of the Criminal Procedure Code and Judex Juris consideration in granting an appeal application in thievery case with violence. Research method used normative law research prescriptive. Sources of law materials used primary law and secondary law, with law materials analysis technique use of syllogisms and interpretation by deductive pattern of thinking. Writer interested to examine a criminal thievery case with violence in Padanng and the name of the defendant is Syafrizal and Hendra Indrian Efanda. Them do the theft use Sumiati’s motorcyclei. Based on Padang District Superior Court's Verdict Number: 92/pid/2014/pt.pdg dated july 3, 2014 the district court upheld the Verdict number: 106/pid.b/2014/pn.pdg dated april 24, 2014 Verdict stated that the evidence Sumiati's motorcycle deprived belonging to the state. Public Prosecutor/ Prosecutor felt the regulations were applied as they should in the form of Verdict that the evidence deprived belonging to the state considered have implemented laws of evidence not as they should. An appeal reasons filed by Public Prosecutor regarding documentary evidence ownership of motor vehicles has been clearly revealed in examining trial at the Padang District Court. Keywords: Material Evidence, Public Prosecutor, Evidence, Thievery